Comparison Between Low Mechanical Index and High Mechanical Index Contrast Modes of Contrast‐Enhanced Ultrasonography: Evaluation of Perfusion Defects of Hypervascular Hepatocellular Carcinomas During the Post–Vascular Phase. (17th January 2019) - Duisyenbi, Zaya; Numata, Kazushi; Nihonmatsu, Hiromi; Fukuda, Hiroyuki; Chuma, Makoto; Kondo, Masaaki; Nozaki, Akito; Tanaka, Katsuaki; Maeda, Shin
Abstract : Objectives: We evaluated the detection rates for perfusion defects in hypervascular hepatocellular carcinomas comparing the low mechanical index (MI) and high MI contrast modes during the post–vascular phase (PVP) of contrast‐enhanced ultrasonography. Methods: Seventy‐eight patients with 84 hypervascular hepatocellular carcinomas (mean diameter, 23.4 ± 11.2 mm) were selected for this retrospective study. All the patients underwent whole‐liver scanning using conventional ultrasonography before injection of a perflubutane‐based contrast agent (Sonazoid), and all the detected nodules were classified as either hypoechoic or hyperechoic nodules. Next, hypoechoic and hyperechoic nodules were evaluated using contrast‐enhanced ultrasonography, and the presence of a perfusion defect was assessed for each nodule using both the low MI (0.2–0.3) and the high MI (0.7–1.2) contrast modes during the PVP (10 minutes after injection). The data were analyzed using the McNemar test. Results: Forty‐four nodules were classified as hypoechoic nodules, and the remaining 40 nodules were classified as hyperechoic nodules using conventional ultrasonography. The detection rate for perfusion defects determined using the high MI contrast mode was higher than that determined using the low MI contrast mode in hyperechoic nodules during the PVP (low MI, 58% [23 of 40]; high MI, 90% [36 of 40]; P  < .0001). However, no significant difference was observed between the low MI and the high MI contrast modes in hypoechoic nodules (low MI, 80% [35 of 44]; high MI, 89% [39 of 44]; P  = .125). Conclusion: Compared with the low MI contrast mode, the high MI contrast mode was more sensitive for detecting perfusion defects in hypervascular hepatocellular carcinomas in patients with hyperechoic nodules during the PVP.